1984
DOI: 10.1016/0302-4598(84)87020-8
|View full text |Cite
|
Sign up to set email alerts
|

Tentative correlation between the electrochemical oxidation of neuroleptics and their pharmacological properties

Abstract: A number of drugs are largely metabolized after oral administration, especially by redox processes. Among the neuroleptics. loxapine. clotiapine and clozapine. which are sevenmembered tricyclic molé cules with a piperazine sidechain. are known to be extensively metabolized by oxidation. An electrochemical study of thèse compounds was initiated in order to détermine their in vitro redox properties and to elucidate their oxidation mechanisms. The measurements were carried out in aqueous and nonaqueous média usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…6A and B, it is proposed that the oxidation involves the piperazine moiety. The redox behaviour of piperazine containing compounds has been previously reported [22][23][24][25][26]. Considering that in acid media piperazine moiety is protonated (pK a1 ~ 7 and pK a2 ~ 3), the electrochemical oxidation of danusertib at peak 3 a occurs with the transfer of two electrons and two protons from the nitrogen atom in the proximity of the methyl group leading to the formation of iminium cation, Scheme 2C, which is hydrolysed forming an amine derivative and formaldehyde [26].…”
Section: Oxidation Mechanismmentioning
confidence: 90%
“…6A and B, it is proposed that the oxidation involves the piperazine moiety. The redox behaviour of piperazine containing compounds has been previously reported [22][23][24][25][26]. Considering that in acid media piperazine moiety is protonated (pK a1 ~ 7 and pK a2 ~ 3), the electrochemical oxidation of danusertib at peak 3 a occurs with the transfer of two electrons and two protons from the nitrogen atom in the proximity of the methyl group leading to the formation of iminium cation, Scheme 2C, which is hydrolysed forming an amine derivative and formaldehyde [26].…”
Section: Oxidation Mechanismmentioning
confidence: 90%
“…It is worthwhile to point out that our previous investigations have shown a possible relationship between the electrooxidation of dibenzazepine analogues and their pharmacological properties . Voltammetric data have permitted to show that the electrooxidation occurred on the tricyclic ring and that the lone pair of electrons on the nitrogen (diazepine nucleus) is more readily available than the electron pairs of sulfur (thiazepine moiety) or oxygen (oxazepine moiety) .…”
Section: Discussionmentioning
confidence: 93%
“…It is worthwhile to point out that our previous investigations have shown a possible relationship between the electrooxidation of dibenzazepine analogues and their pharmacological properties. 44 Voltammetric data have permitted to show that the electrooxidation occurred on the tricyclic ring and that the lone pair of electrons on the nitrogen (diazepine nucleus) is more readily available than the electron pairs of sulfur (thiazepine moiety) or oxygen (oxazepine moiety). 45 In the present work, although the detailed mechanism by which the electrooxidation of the investigated drugs occurs is currently unknown, the electrooxidation potential along with all the studied parameters can be regarded as valuable data in developing new tricyclic analogues with increased safety.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, d 10 metal complexes have attracted much interest in recent years, not only because of their interesting structures but also because of their photoluminescence properties [12,13]. Although there have been several reports on the electrochemical behavior of piperazine molecules [14][15][16][17], study of their anodic oxidation in a coordinated polymer has not been reported. In this paper we report the preparation, crystal structure, IR spectroscopy, thermal stability, and the luminescence and electrochemical properties of a novel cadmium coordination polymer [Cd(pipH)(Cl)(l-Cl) 2 ] n ÁnH 2 O.…”
Section: Introductionmentioning
confidence: 99%